Influence of treatment with and without extractions on the growth pattern of dolichofacial patients - Vanessa Scherer Porto; José Fernando Castanha Henriques; Guilherme Janson; Marcos Roberto de Freitas; Arnaldo Pinzan (Dental Press Editora, 2012)
OBJECTIVE: The objective of this retrospective study was to compare, by means of lateral cephalograms, the facial growth pattern changes due to the treatment with and without extractions of four first premolars in dolichofacial individuals. METHODS: Groups 1 and 2 were constituted of 23 dolichofacial patients each, with Class II malocclusion, division 1 and initial age average of 12.36 and 12.29 years, respectively. Patients from Group 1 were treated without extractions and Group 2 was treated with extraction of the four first premolars, given that both used occipital headgear. Groups were compatibilized according to age, treatment period, gender and malocclusion severity. The t test was applied for intergroups comparison. RESULTS: Most variables (SN.PP, SN.Ocl and FMA) did not present statistically significant difference between groups. CONCLUSION: Although the treatment with extractions tend to reduce the mandibular plane angle (SN.GoGn) and the facial axis (NS.Gn), the analyzed treatment protocols did not affect in a clinically relevant way the facial growth pattern. OBJETIVO: o objetivo desse estudo retrospectivo foi comparar, por meio de telerradiografias, as alterações no padrão de crescimento facial decorrentes do tratamento sem e com extrações dos quatro primeiros pré-molares em indivíduos dolicofaciais. MÉTODOS: os grupos 1 e 2 foram constituídos, cada um, por 23 pacientes dolicofaciais com má oclusão Classe II, divisão 1 e idade inicial média de 12,36 e 12,29 anos, respectivamente. Os pacientes do grupo 1 foram tratados sem extrações e os do grupo 2 foram tratados com extrações dos quatro primeiros pré-molares, sendo que ambos utilizaram aparelho extrabucal occipital. Os grupos foram compatibilizados de acordo com a idade, tempo de tratamento, sexo e severidade da má oclusão. O teste t foi aplicado para a comparação intergrupos. RESULTADOS: a maioria das variáveis (SN.PP, SN.Ocl e FMA) não apresentou diferença estatisticamente significativa entre os grupos. CONCLUSÃO: apesar do tratamento com extrações tender a reduzir a inclinação do plano mandibular (SN.GoGn) e o eixo facial (NS.Gn), os protocolos de tratamento analisados não alteraram de forma clinicamente relevante o padrão de crescimento facial.